Pregnancy in adolescence: a propositive study on public policies to combat factors that cause the process (Research, Society and Development, 2021)
This research has as objective to understand the actions that enable the reduction of self indices of teenage pregnancy and to describe the public policies already constituted to prevent these factors. The study was elaborated by means of a bibliographic and documental research with a descriptive approach carried out in the virtual data platform SCIELO as well as in national documents present in the current legal system. The result presented relates the understanding of public policies for the prevention of the process of pregnancy in adolescence, as well as a critical/reflective analysis of the fulfillment of these policies in primary care.